Development of Internal Audit - LAMBEKOVA, Aigerim; NURGALIEVA, Aliya; SYZDYKOVA, Elmira; ZHANIBEKOVA, Gaukhar; AFF, Josef (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).19, 2018)
The internal audit service is not just a world trend, but an extreme necessity in the face of actively developing and more complicated economic relations. The purpose of this article is to identify the main problems of internal audit in Russia and Kazakhstan. It is argued that the notion of the correctness of internal audit provides conceptual tools for the study of internal audit as a disciplinary mechanism in the conditions of corporate governance of modern organizations. The article develops the initial conceptual formulation and internal audit, audits and controls to improve the rationality of economic activity and related control measures.